Improvement on Growth, Yield, Economics and Soil Fertility Status of Blackgram (Vigna mungo L.) Under Integrated Nutrient Management - Samant, Tiryak Kumar; Mishra, Debasis (International Journal of Bio-resource and Stress Management, 2023)
An On-farm Trial (OFT) was conducted during rabi season of 2016–17 at farmers’ field in Ragudiapada village of Angul district in Odisha, India using randomized block design with ten replications to study the improvement on growth, yield, economics and soil fertility status of blackgram under integrated nutrient management. The results indicated that 75% STBFR+FYM @ 2.0 t ha-1 incubated with PSB @ 5 kg ha-1+seed inoculation of Rhizobium culture @ 20 g kg-1 of seed+sodium molybdate @ 0.3 g kg-1 of seed recorded significantly higher plant height(43.52 cm),branches plant-1 (4.85), nodules plant-1 (22.75), pods plant-1 (21.2), seeds pod-1 (6.19), grain yield (6.45 q ha-1) and harvest index (37.2%). The same treatment fetched higher gross return of ` 32787 ha-1 with a benefit– cost ratio of 1.67 and additional net return of ` 4861 ha-1 as compared STBF. With regards to soil fertility after crop harvest, the same treatment resulted in the highest soil available nitrogen (220.8 kg ha-1), phosphorus (12.07 kg ha-1) and potassium (193.05 kg ha-1) which was 14.3, 11.8,9.7% higher over the initial soil status, respectively. Thus, 75% STBFR+FYM @ 2.0 t ha-1incubated with PSB @ 5 kg ha-1+seed inoculation of Rhizobium culture @ 20g kg-1 of seed+sodium molybdate @ 0.3 g kg-1 of seed is the proven technology which is effective for higher crop growth, yield, profitability and soil fertility status of blackgram under mid central table land zone of Odisha.